Aplicação web para gerenciamento de dados e dispositivos IOT no contexto da agricultura de precisão - Franz, Felipe Hister (2022)
The constant increase in the world population generates a great demand for food, which ends up stimulating the agricultural sector to look for ways to increase productivity. By using applications based on precision agriculture, it is possible to collect and analyze various information from the feld, to increase productivity and mitigate costs and environmental impacts, by consuming natural resources more effciently. Precision agriculture uses the internet of things (IoT) and sensor networks to provide tools and software that collect and analyze information from the feld, helping to solve agricultural problems, such as optimizing production, irrigation and pest control. Typically software in the free version provides few tools and has limited functionality. In this scenario, it becomes important to provide easily accessible web applications that allow for more accurate and rapid management of agricultural properties, maximizing decision-making. The objective of this work was to develop a web application to assist in the control and management of agricultural properties, allowing the planning of IoT networks. The analysis of the data obtained by the sensors through the generation of thematic maps and graphics, allowed the farmer to control soil management and the IoT devices installed on the agricultural property. The application was developed for a web environment in order to facilitate access by users, being able to be accessed from any location without the need for installation and thus making it available for free for use. The application uses the AgDataBox application programming interface (API), which integrates data from applications that are part of the AgDataBox project, so data can be generated and used by any of the applications provided by the platform. The observed results show that it was possible to evaluate the web application and its functionalities, to plan an IoT network, analyze the data obtained by the sensors through graphs and thematic maps that were interpolated using interpolators (the inverse of the weighted distance and kriging ordinary). Additionally, the free web application demonstrated satisfactory performance for the practice of precisión agriculture.